2011
DOI: 10.1016/j.ygcen.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating salmon 28- and 22-kDa insulin-like growth factor binding proteins (IGFBPs) are co-orthologs of IGFBP-1

Abstract: Circulating insulin-like growth factor binding proteins (IGFBPs) play pivotal roles in stabilizing IGFs and regulating their availability to target tissues. In the teleost circulation, three major IGFBPs are typically detected by ligand blotting with molecular masses around 20-25, 28-32 and 40-45 kDa. However, their identity is poorly established and often confused. We previously identified salmon 22-and 41-kDa forms as IGFBP-1 and-2b, respectively. In the present study, we cloned the cDNA of 28-kDa IGFBP from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 51 publications
5
73
0
Order By: Relevance
“…Total RNA was extracted from the tissues as described in Shimizu et al (45). RNA (1.5 g) was reverse-transcribed using SuperScript VILO cDNA Synthesis kit (Invitrogen, Carlsbad, CA) in a 10-l reaction according to the manufacturer's instruction.…”
Section: Fishmentioning
confidence: 99%
“…Total RNA was extracted from the tissues as described in Shimizu et al (45). RNA (1.5 g) was reverse-transcribed using SuperScript VILO cDNA Synthesis kit (Invitrogen, Carlsbad, CA) in a 10-l reaction according to the manufacturer's instruction.…”
Section: Fishmentioning
confidence: 99%
“…These results suggested that the inhibitory effect of fish IGFBP-2 mainly do not depend on the RGD and HBD motifs, but by binding to IGFs. Because of the additional genome duplication, the duplicate copies of IGFBP-2 (IGFBP-2a and IGFBP2b) have been reported in many teleosts, including zebra fish, tetraodon, chinook salmon, and Japanese founder (Duan et al 1999;Zhou et al 2008;Rodgers et al 2008;Shimizu et al 2011;Zhang et al 2013). Although the IGFBP-2a and IGFBP-2b shared highly degree identity, they displayed district expression pattern in different tissues, embryogenesis and physiological status Shimizu et al 2011;Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The similar result was also observed in chinook salmon. The salmon IGFBP-2b had three N-glycosylation sites, and IGFBP-2a had only one (Shimizu et al 2011). However, the N-glycosylation did not exist in all fish IGFBP-2 and the numbers of the putative N-glycosylation sites of other fish IGFBP-2 was 3(zebra fish IGFBP-2a), 1(common carp), 1(tetraodon IGFBP-2a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations